Effects of Silica Level on Some Properties of Oryza sativa Straw and Hull - Balasta, Maria Luisa F. C.; Perez, Consuelo M.; Juliano, Bienvenido O.; Vlllareal, Corazón P.; Lott, John N. A.; Roxas, Domingo B. (Canadian Science Publishing, 1989)
Reduction of silica content of two rice varieties obtained by growth in hydroponic solutions (0–400 ppm added SiO2) increased leaf openness and decreased both stem bending hardness and hull weight. The number of silica bodies in the surface of leaf blades was similarly decreased. Mapping by energy dispersive X-ray analysis techniques showed high concentrations of silicon in silica bodies inside silica cells on leaf blades and uniform distribution on lemma and palea surfaces. Vascular tissues and bulliform cells were also rich in silica. Decrease in silica content to less than 10% dry weight increased the in vivo dry matter digestibility of straw in both varieties and increased the in vitro organic matter digestibility of IR36 straw.